Sequential phosphine-catalyzed, nucleophilic thiol ene/radical-mediated thiol-yne reactions and the facile orthogonal synthesis of polyfunctional materials - Chan, J.; Hoyle, C.; Lowe, Andrew (American Chemical Society, 2009)
The first example of highly efficient sequential thiol-ene/thiol-yne reactions conducted in an orthogonal manner is presented and its broad application in the synthesis of polyfunctional materials demonstrated. The anionic chain mechanism of the phosphine-mediated thiol-ene reaction is highlighted, as is the radical-mediated thiol-yne reaction. Kinetic data for a model reaction are presented, followed by a discussion of the synthesis of a range of materials with diverse functionality, including an example of potential biomedical significance. © 2009 American Chemical Society.